Study on the development of a fuzzy logic control electromagnetic actuated CVT system - Sharif, Sazzad; Rahman, Mohammed Ataur; Mohiuddin, A. K. M.; Hossain, Altab (2011)
This paper conducts the preliminary research of an Electromagnetic Actuated Continuously Variable Transmission (EMA-CVT) system of quarter scale. An EMA-CVT system is consisted of two pairs of electromagnetic actuators (solenoid)attached with primary and secondary pulley in order to develop the attraction and repulsive forces. The relationships between the speed ratio and electromagnetic actuation and clamping force and output torque of the CVT are established based on the kinematics of the EMA-CVT system. This study also focused on fuzzy logic based controller (FLC) to precise control for pushing and pulling the sheaves based on the feedback of the RPM sensor and slope sensor. The EMA-CVT performance with controller is 28% more than that of the EMA-CVT without controller. The solenoids of the EMA were activated by varying the current supply with the Fuzzy-Proportional-Derivative-Integrator (FPID)to maintain the non-linearity of the CVT in response of the vehicle traction torque demand. Result shows that the solenoid able to pull the plunger in the desired distance with supply current of 12.5 amp while push the plunger to the desired distance with 14.00 amp current supply to the windings when the vehicle is considered in 10% grad. The acceleration time of the ¼ scale car has been recorded as 5.5 s with the response of drive wheels torque.